Analisis Faktor - Faktor Yang Mempengaruhi Kredit Macet Pada Koperasi Pintu Air - Helena Rosalia Parera; Maria Jelita Via (Program Studi Pendidikan Ekonomi FKIP Universitas Flores, 2025)
This research aims to analyze the financing management in cooperatives and the factors influencing bad credit. The methodology used in this study is a quantitative approach with data collection techniques through questionnaires distributed to cooperative members. The results show that cooperative financing management is significantly influenced by internal factors such as risk management, credit policy, and monitoring, as well as external factors like economic conditions and government policies. Further discussion indicates that enhancing risk management strategies and implementing stricter credit policies can reduce the risk of bad credit. The conclusion of this research emphasizes the importance of improving financing management and credit policies in cooperatives to increase their stability and sustainability.